2011
DOI: 10.1097/mnm.0b013e3283412ef5
|View full text |Cite
|
Sign up to set email alerts
|

18F-fluoride PET/CT for assessing bone involvement in prostate and breast cancers

Abstract: Objective To evaluate the accuracy of 18 F-fluoride PET/computed tomography (CT) to detect bone metastases (BMs) in a breast and prostate cancer population, using magnetic resonance imaging (MRI) or thin-slice CT as a gold standard.Methods We have prospectively included 34 patients with breast (N = 24) or prostate cancer (N = 10) at high risk of BMs. Whole-body PET/CT (low-dose CT) and bone scintigraphy (BS) with single photon emission CT were obtained for all 34 patients and the results compared with a radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…Nonetheless, 18 F-fluoride PET/CT showed fewer false-positive findings than conventional bone scanning in the detection of bony metastases (5,19). Besides, inappropriate treatment due to false-positive findings can be minimized via a thorough discussion of cases in a multidisciplinary tumor board.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, 18 F-fluoride PET/CT showed fewer false-positive findings than conventional bone scanning in the detection of bony metastases (5,19). Besides, inappropriate treatment due to false-positive findings can be minimized via a thorough discussion of cases in a multidisciplinary tumor board.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the transition to the better resolution of PET/CT for detection of osseous metastases appears appealing, with 18 F 2 as the radiotracer of choice. 18 F 2 PET/CT is superior to 99m Tc-MDP planar scintigraphy and SPECT for bone lesion detection (17)(18)(19)(20). Semiquantitative analysis based on 18 F 2 PET/CT is also more accurate than 99m Tc-MDP SPECT for assessing the response to treatment of bone metastases (21).…”
Section: Discussionmentioning
confidence: 99%
“…PET and PET/CT studies in metastatic breast cancer have shown improved diagnostic accuracy compared with that of BS (33)(34)(35)(36)(37) or CT (38), and 18 F-NaF PET/CT has shown higher diagnostic accuracy than 18 F-NaF PET without the CT component (35). Similar improvements in diagnostic accuracy over that of BS with or without SPECT have been replicated in other cancers, including prostate cancer (39)(40)(41), lung cancer (42), renal cancer (43), bladder cancer (44), and hepatocellular carcinoma (45).…”
Section: F-naf Petmentioning
confidence: 99%